The probability map of the universe essays on David Albert's Time and chance - Loewer, Barry 1945-; Weslake, Brad; Winsberg, Eric 1968- (Harvard University Press, 2023)
"David Albert's 2000 book Time and Chance attempts to account for some of the most intractable problems in theoretical physics, in particular those arising from the direction of time. This collection assembles essays exploring and debating Albert's ideas, now recognized as among the most important recent contributions to the philosophy of science"--
Keywords: Albert, David Z. -- 1954- -- Time and chance; Albert, David Z.; Physics / Philosophy; Time reversal; Aufsatzsammlung